Expressions of P-glycoprotein in treatment: Resistant Helicobacter pylori patients - Omar, Marhanis; Crowe, Andrew; Tay, C.; Hughes, Jeff (Elsevier, 2014)
Objective: There is an increasing incidence of Helicobacter pylori eradication therapy failure secondary to antibiotic resistance. In this study, we aimed to assess the P-glycoprotein expression levels among subjects who were H. pylori-positive and received multiple courses of eradication therapy to understand factors that may associate with their non-responses. Methods: Eleven resistant subjects were recruited during their hospital visit for upper gastrointestinal endoscopies. H. pylori infection status was confirmed by rapid urease test and bacterial culture. P-glycoprotein expressions from the antral and duodenal biopsies were measured by Western blot. The data was compared with H. pylori-negative (n = 54) and H. pylori-positive-treatment naïve (n = 22) that were recruited earlier in another study. Results: The resistant group showed higher relative antral P-glycoprotein expression com-pared to the H. pylori-negative group ( p = 0.0361). Most subjects demonstrated resistance to clarithromycin (72%), metronidazole (63.6%) or both (54.5%). No significant difference was observed between the P-glycoprotein expression in H. pylori-treatment resistant and H. pylori-positive-treatment naïve groups ( p = 0.319). Conclusion: H. pylori infection induces the expression of P-glycoprotein in the antrum. This study shows a potential protective mechanism which may be exploited through the use of P-glycoprotein inducers, such as rifabutin, may be beneficial in eradication regimens.